PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA MTs. MA’ARIF SIDOMUKTI GRESIK - Muhammad Arif Syihabuddin; Rizky Amalia (Institut Keislaman Abdullah Faqih Gresik, 2022)
Abstract: This study discusses about the Model of Teaching that is often used by educators in the learning process. Educators are required to choose a Model of Teaching that makes students more active and also improves student learning outcomes. One of the Model of Teaching that can be used is Student Team Achievement Divisions (STAD). The purpose of this study was to determine whether there was an effect of the STAD type cooperative learning model on student learning outcomes at Mts. Ma'arif Sidomukti, and to find out how much influence the STAD type cooperative learning model had on student learning outcomes in Mts. Ma'arif Sidomukti. This study uses a quantitative experimental research method using a Pre-Experimental Design, with a One-Group Pretest-Posttest Design. From the results of the analysis of hypothesis testing, it is known that there is a significant influence in the learning process using the STAD type cooperative learning model on student learning outcomes at Mts. Ma'arif Sidomukti. And it is known from the results of the determinant coefficient that the effect of the STAD type cooperative learning model on student learning outcomes in Aqidah Akhlak subjects is 93%.Keyword: Model of Teaching, Cooperative Learning, Student Team Achievement Divisions (STAD).